2013
DOI: 10.1364/ol.38.002629
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of the interaction of low-frequency electric fields with biological tissues by optical coherence tomography

Abstract: Low-frequency electric fields propagating in ex vivo biological tissues have been observed by using double-correlation optical coherence tomography (OCT). An adaptive Wiener filtering approach has been used to remove background noise, and a Fourier domain correlation algorithm has been applied to the sequence of OCT images. The results present the first direct observation (to our knowledge) of the scope of the electric field influencing biological tissues with OCT. The results show that variation in voltage an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…such as Optical Coherence Tomography (OCT), have been received considerable attention among other diagnostic modalities. Nowadays, OCT is extensively used in a number of applications , including visualization of spatial distribution of subcutaneous blood vessels in human skin , visualization of molecular diffusion within the biological tissues , electro‐kinetic response of biological tissues ex vivo and others. Polarization‐sensitive OCT enables detection of birefringent properties of human tissues and has been successfully used for characterization of Achilles ruptured tendons and cartilage tissue .…”
Section: Introductionmentioning
confidence: 99%
“…such as Optical Coherence Tomography (OCT), have been received considerable attention among other diagnostic modalities. Nowadays, OCT is extensively used in a number of applications , including visualization of spatial distribution of subcutaneous blood vessels in human skin , visualization of molecular diffusion within the biological tissues , electro‐kinetic response of biological tissues ex vivo and others. Polarization‐sensitive OCT enables detection of birefringent properties of human tissues and has been successfully used for characterization of Achilles ruptured tendons and cartilage tissue .…”
Section: Introductionmentioning
confidence: 99%
“…26 Following substraction of an estimate of the noise from the original OCT images, the cross-correlation between two grids is calculated as 10,13 Cðx; zÞ 26 Following substraction of an estimate of the noise from the original OCT images, the cross-correlation between two grids is calculated as 10,13 Cðx; zÞ…”
Section: Methodsmentioning
confidence: 99%
“…5,6 By using spatial and/or temporal analysis of the dynamic speckle patterns generated by moving red blood cells, various OCT modifications for visualization of subcutaneous blood vessels' distribution in human skin in vivo have been suggested, including speckle variance OCT (svOCT), 7 optical microangiography (OMAG), 8 correlation map OCT (cmOCT), 9 and double correlation OCT (dcOCT). 13 In the current paper, we present the results of further OCT studies of the electro-kinetic response of biological tissues influenced by a low-frequency electric field at normal conditions and upon the topical application of optical clearing agents (OCAs). 13 In the current paper, we present the results of further OCT studies of the electro-kinetic response of biological tissues influenced by a low-frequency electric field at normal conditions and upon the topical application of optical clearing agents (OCAs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further investigations [13] revealed that the amplitude of the OCT signal change varied with the magnitude of the applied field and was inversely proportional to its frequency. More recently, Peña et al [14] used OCT amplitude images to visualize the propagation of low-frequency electric field in tissue samples ex vivo, invoking the mechanism of electrically induced optical changes (EIOC) related to the electrokinetic properties of tissue [14].…”
mentioning
confidence: 99%